2015
DOI: 10.1186/s12931-015-0218-2
|View full text |Cite
|
Sign up to set email alerts
|

Periostin: its role in asthma and its potential as a diagnostic or therapeutic target

Abstract: Accumulating evidence shows that periostin, a matricellular protein, is involved in many fundamental biological processes such as cell proliferation, cell invasion, and angiogenesis. Changes in periostin expression are commonly detected in various cancers and pre-cancerous conditions, and periostin may be involved in regulating a diverse set of cancer cell activities that contribute to tumorigenesis, cancer progression, and metastasis. Periostin has also been shown to be involved in many aspects of allergic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 70 publications
(136 reference statements)
4
67
1
Order By: Relevance
“…These data are supported by previous work showing that deficiency or inhibition of periostin prevents the development or progression of many allergic inflammatory diseases including allergic dermatitis, asthma and chronic rhinosinusitis. 44, 45 The presence of periostin in an inflammatory or injured environment appears to impart competency for macrophages to infiltrate and further impact disease.…”
Section: Discussionmentioning
confidence: 99%
“…These data are supported by previous work showing that deficiency or inhibition of periostin prevents the development or progression of many allergic inflammatory diseases including allergic dermatitis, asthma and chronic rhinosinusitis. 44, 45 The presence of periostin in an inflammatory or injured environment appears to impart competency for macrophages to infiltrate and further impact disease.…”
Section: Discussionmentioning
confidence: 99%
“…Isoforms of periostin also exist due to alternative splicing and have been linked to cancers (249). In addition, periostin has been associated with numerous pathological conditions including asthma, skin disorders, polycystic kidney disease, and cardiovascular disease (247, 250254). …”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, it is well recognized that the thickening of the epithelial-connective tissue interface in asthma is the consequence of excessive deposits of collagen types I, III, and V, associated to fibronectin and tenascin-C. Periostin identification in the same location as these extracellular matrix protein supports the assertion that they represent different components of the bronchial subepithelial fibrosis [9,16]. These initial observations have been later completed by other studies which revealed an increased periostin serum or sputum level in patients with allergic bronchial asthma [12,17,18]. Thus, an increased periostin level associated with eosinophilia and Th2 mediated inflammation is seen in a specific type of bronchial asthma.…”
Section: Periostin and Bronchial Asthmamentioning
confidence: 84%
“…It appears that periostin enhanced expression is responsible for the induction of eosinophils recruitment in bronchial wall [12] and its ability to act as α v β 3 , α v β 5 , α 4 β 6 , and α M β 2 (CD11b) integrin ligand increases eosinophils adherence to fibronectin [25][26][27].…”
Section: Periostin and Bronchial Asthmamentioning
confidence: 99%
See 1 more Smart Citation